Analisis Pengetahuan dan Sikap Pekerja Pembakar Tandan Kosong Kelapa Sawit (TTKS) Terhadap Resiko Kesehatan Akibat Pencemaran Udara di Desa Teluk Mega Kabupaten Rokan Hilir - Riski Novera Yenita; M. Luqman Fajri (Jurnal Zona, 2025)
Oil palm empty fruit bunches are one of the by-products of the Crude Palm Oil (CPO) agro-industry, in addition to shells, POME, sludge and solid decanter. The number of empty oil palm fruit bunches is very abundant, along with the increasing number of palm fruit and CPO produced. This study aims to determine whether there is a relationship between the level of knowledge and attitudes of workers burning empty fruit bunches of oil palm (TKKS) on health risks due to air pollution in Teluk Mega Village, Tanah Putih District, Rokan Hilir Regency. This type of research is quantitative and cross sectional design. The population is workers and the sample is 32 people, with Total Sampling. The research instrument is a questionnaire. Data analysis used univariate and bivariate. Univariate results show that most respondents have less knowledge as much as 62.5%, have a negative attitude about anemia as much as 59.4%, and some respondents have a risk of disease due to air pollution as much as 37.5%. Bivariate results show the level of knowledge of Oil Palm Empty Bunch Burners (TKKS) on health risks due to air pollution in Teluk Mega Village, Tanah Putih District, Rokan Hilir Regency, Pvalue 0.030 0.05 and there is an attitude of Oil Palm Empty Fruit Bunches (TKKS) workers. on health risks due to air pollution in Teluk Mega Village, Tanah Putih Subdistrict, Rokan Hilir Regency P value 0.008 0.05 It is expected that empty bunches burners pay attention to their health by using personal protective equipment such as masks, glasses and other people to avoid air pollution in the workplace